Analysis of the Error Propagation Phenomenon in Network Structures - Król, Dariusz; Kukla, Grzegorz (Computing and Informatics, 2012)
The analysis of error propagation is of fundamental importance to assure safe operation and management of abnormal situations in any distributed information system. In this paper, the quantitative and qualitative methods are proposed to analyze possible error propagation scenarios based on different topologies, error types and probability distributions. The most interesting from our point of view is the course of error propagation in simple structures that are contained in more complex ones. These complex structures, which have attracted the attention of scientists for many decades, are traditionally analyzed with the use of formalisms from graph theory. Certain types of graphs are often used to model naturally occurring complex structures, such as social networks. Graph-theoretic approach proved successful when applied to social networks and other naturally occurring complex networks. The research was verified based on the experiments conducted on simulation model. The results provide some ideas of robustness -- the knowledge how to design the most error resistant architectures in complex environments.